Adjectives in Destination Promotion Texts - Thu, Dinh Quoc Anh (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
As tourism texts act as an important source of information for prospective tourists, this paper looks into the use of adjectives in English tourism texts by analyzing a small, specialized corpus of texts promoting destinations. The self-compiled corpus had its data taken from the official tourism website of Vietnam. Using TermoStat Web 3.0 (Drouin, 2003) and Antconc (Anthony, 2011) to identify adjectives in the corpus, the study seeks to explore adjectival usage in a discourse which is known for its hyperbolic language and offers a better understanding of ways adjectives help create persuasive texts. Results revealed a high percentage of adjectives in the analyzed texts. Besides, the extensive use and high selectivity of adjectives in the corpus help paint a complete picture of the destinations being described, hence connect those places with the reader. Notably, compound adjectives were found to be widely utilized for compact but detailed expressions. The findings are beneficial to instructors and learners of English for tourism and English writing as well as translation training and practice.